Pengembangan Aplikasi Jasa Service Peralatan Elektronik Berbasis Android Menggunakan Payment Gateways - Ferdinan, Rasid; Fachrie, Muhammad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Along with the development of current technology such as TV repair, fans, refrigerators, washing machines, irons, air conditioners do not always function properly. There are times when a device is damaged and the user of the device will try to fix it by visiting a service or repair shop for televisions, fans, refrigerators, washing machines, irons and air conditioners. Of course, in this case the user will waste time and energy to go to the service place. Therefore, online booking services such as Grab and Gojek are needed. This online booking service specifically accepts the repair of televisions, fans, refrigerators, washing machines, irons, air conditioners, directly so that device users can save time and costs. With the selection of categories based on electronic products, it is easier for users if they want to find a service based on the electronic equipment that the user wants to repair. This application will be equipped with an online payment system integrated with Midtrans as a payment gateway service provider so that the transaction process becomes faster, easier and more practical.